Relative age effect in young Swiss alpine skiers from 2004 to 2011 - Gorski, T.; Rosser, T.; Hoppeler, H.; Vogt, M. (International Journal of Sports Physiology and Performance, 2016)
Purpose: To verify whether relative age effects (RAEs) occur among young male and female Swiss Alpine skiers of different age groups and performance levels. In addition, the efficacy of normalizing performance in physical tests to height and body mass to attenuate RAEs eventually present was tested.